(untitled) (Al-Mansour Journal, 2022)
A number of haptic devices have been developed that give one the sensation of touching something literally... while it is basically a mechanical or digital control mechanism that relays tactile sensations between the toucher and the touched object. This technology will allow blind people to be able to touch the scene or object displayed on the screen, using a matrix of steel rods to represent each bit of information displayed on the screen to be a physically touchable object instead of virtual information can only be seen on the screen. One to explore a number of avenues with tactile feedback mechanisms they will allow us to feel things we have never felt. It also is going to make dramatic changes in education, medical practice, surgery, training in various disciplines.